Nacionalni park Mljet - Šantek, Goran Pavel (Traditiones (Ljubljana), 2013)
This paper outlines the differences between park residents and management in visualizing the purpose and function of Mljet National Park. These differencesare mainly due to their distinctly oriented interests, and potential causes of conflict emerge from prohibitions and legislative acts imposed by the park. The centuries-old tradition of fishing is now greatly reduced by the park's restrictive laws and questions are being raised about how to reconcile the interests of local community with the park's mission of heritage and nature protection.
Keywords: ethnology; Kulturna dediščina; folk culture; Naravna dediščina; Narodni parki; cultural heritage; natural heritage; management; Upravljanje; Nacionalni park Mljet; Croatia; Hrvaška; Etnologija; Ljudska kultura; Ribištvo